Decoding digital trust: A multi-dimensional analysis of tech influencer credibility on YouTube - Floether, Kevin (My University, 2024)
There is a growing body of literature on the importance of corporate reputation and reputation management, but an insufficient amount of research that looks at rebuilding and repairing corporate reputation. While many executives agree that reputation is critical, how to repair and rebuild it is absent from in the literature. This study includes a comprehensive literature review, in-depth interviews with five senior communications managers, content analyses of nine organizations, and an online survey of communications and public relations practitioners. The results of this study strongly suggest that reputation management is a top priority amongst Canadian organizations. The results also indicate that the majority of survey participants and interviewees use multiple tools to monitor and measure reputation. The interview results demonstrated that communications teams had representation at the executive level. This study highlights the need for a standardized method to measure reputation.
Keywords: tech influencers; trust measurement; social media marketing; content analysis; sentiment analysis; media portrayal; YouTube; influencer credibility; consumer opinions; digital trust